Nature of electrophilic oxygen: insights from periodic density functional theory investigations - Kenge, Nivedita; Pitale, Sameer; Joshi, Kavita (Surface Science, 2019)
Increasing demand of ethylene oxide and the cost of versatile chemical ethene has been a driving force for understanding mechanism of epoxidation to develop highly selective catalytic process. Direct epoxidation is a proposed mechanism which in theory provides 100% selectivity. A key aspect of this mechanism is an electrophilic oxygen (O-ele) species forming on the Ag surface. In the past two and half decades, large number of theoretical and experimental investigations have tried to elucidate formation of O-ele, on Ag surface with little success. Equipped with this rich literature on Ag-O interactions, we investigate the same using periodic DFT calculations to further understand how silver surface and oxygen interact with each other from a chemical standpoint. Based on energetics, Lowdin charges, topologies and pdos data described in this study, we scrutinize the established notions of O-ele. Our study provides no evidence in support of O-ele, being an atomic species nor a diatomic molecular species. In fact, a triatomic molecular species described in this work bears multiple signatures which are very convincing evidence for considering it as the most sought for electrophilic entity.
Keywords: Ag(100); DFT; Electrophilic; epoxidation; Nucleophilic oxygen